Analisis Perilaku Bullyng terhadap Gangguan Mental Siswa di SMP Negeri 35 Medan - Al Firman Mangunsong; Chairun Nisa; Muthiah Lathifah; Ruth Yessika Siahaan; Salwa Andini; Abdinur Batubara (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Humans are called social creatures because in life there is always a process of interaction between fellow humans. Each individual has different conflicts, starting from conflicts in the interaction process, violent conflicts, both verbal and non-verbal violence. At SMP 35 Medan, there have been increasing reports of cases of bullying among students. This behavior includes various forms of physical, verbal, social violence and even cyberbullying. The method used in this research is qualitative, a research model that uses descriptive data in the form of written or spoken language from people and actors who can be observed. This qualitative research is conducted to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs and perceptions. The research results refer to. The impact of bullying on mental health is a serious problem that can affect victims in various aspects of their lives. Studies show that the experience of being a victim of bullying can have a significant negative impact on an individual's mental health, especially in children and adolescents.